Peningkatan Ekonomi Masyarakat Lokal melalui Pemanfaatan Mangrove Ramah Lingkungan Dikampung Nasem Kabupaten Merauke - Sunarni Sunarni; Ratna Purwanti; Sajriawati Sajriawati (Pusat Riset dan Inovasi Nasional, 2025)
Nasem is an indigenous Papuan village endowed with coastal resources, particularly mangrove forests, which possess considerable potential for sustainable utilization. Preliminary observations indicated that the local community had not previously engaged in any form of mangrove use. To address challenges related to mangrove utilization and conservation—both to support ecosystem sustainability and to improve the livelihoods of coastal residents—a community service program was implemented. The program focused on raising awareness of the ecological and economic importance of mangroves through environmentally friendly practices, specifically training in ecoprint production using mangrove leaves. The activities were conducted at the Nasem village hall and involved local community members as participants. The implementation followed three main stages: preparation, process, and outcomes. Educational sessions highlighted the role of mangroves in maintaining environmental balance as well as their benefits for local communities. As ecoprint product training had never been introduced in Nasem, participants demonstrated high levels of enthusiasm and engagement. Evaluation results showed a 90% increase in knowledge regarding ecoprint and revealed that 85% of participants were able to independently produce ecoprint products by creatively designing patterns from mangrove leaves.